The fractured messaging of the National Collegiate Athletic Association and its members in response to COVID-19 - Mirabito, T.; Hardin, R.; Pate, J. R. (International Journal of Sport Communication, 2020)
Dr. Anthony Fauci, director of the National Institute of Allergy and Infectious Diseases and one of the faces of the White House Coronavirus Task Force charged with spearheading the United States` response to COVID-19, said in an interview on April 15, 2020, that he believed sports could return in the summer of 2020 if they implemented comprehensive health and safety accommodations (Hamby, 2020). Two of the most notable alterations that he suggested were substantial amounts of testing and games being played "behind closed doors" (Cancian, 2020, para 1). Testing would likely be within the capacity of major sport leagues, as long as tests were made available to them (Goldman, 2020). A point of contention early in the response to the coronavirus outbreak, ironically, was the National Basketball Association`s (NBA) ability to secure tests for players who demonstrated symptoms of COVID-19, while other Americans did not appear to have similar access (Zillgitt, 2020). Fauci`s second recommendation of physically sequestering fans from games and events would present another unprecedented requirement in a response that has already realized unparalleled circumstances.